Search for narrow resonances in proton-proton collisions at sqrts = 8 TeV decaying to z and higgs bosons in the two tau leptons and a merged jet pair final state - Bernardes, César Augusto (2015)
We present a search in the CMS detector for a high-mass and narrow resonance decaying into a Higgs and a Z SM bosons in the final state with a pair of tau leptons and a pair of quarks. We analyze 19:7=fb of integrated luminosity of? s = 8 TeV proton-proton collisions from LHC. In the resonance mass range of interest (1:0 .. 2:5 TeV), the Z and Higgs bosons are produced with large momentum compared with their masses, which implies that the final products of the two quarks and the two taus must be detected within a small angular separation (boosted topology). Jet substructure techniques are used to identify the boosted Z boson decaying hadronically and a modified approach is considered to reconstruct very collimated pairs of tau leptons from boosted Higgs decay. From a combination of all possible decay modes of the tau lepton, heavy spin-1 resonances production cross sections are excluded at 95% C.L. in a range between 0:9 and 27:8 fb, depending on the resonance mass. We consider as benchmark model an effective description of a strongly coupled theory based on the Minimal Composite Higgs Model, which predicts heavy resonances with suppressed branching fractions into fermions. Comparing the experimental limits with analytical expressions of the parameters of a simplified model Lagrangian we obtain observed limits on these parameters, which are directly connected with the heavy resonance production and decay.